A simple plasma diagnostic based on processing the electrical signals from coaxial discharges - Bruzzone, Horacio Abel (2006)
A technique for the determination of the inductance evolution in coaxial discharges based on measurements of the voltage between the electrodes and of the discharge current time derivative is presented and discussed. The technique is applied to measurements performed in a 5.7 kJ plasma focus device operating with deuterium filling in the 1–6 mbar range (which is the neutron yield range) and the obtained results are in good agreement with the expected evolution of a current sheet within the electrodes system.